2001
DOI: 10.1046/j.1360-0443.2001.969130710.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and extra‐familial influences on alcohol and drug misuse: a twin study of gene–environment correlation

Abstract: Genotype-environment correlations, in particular, moral-religious emphases in the home, appear to be important in the development of substance misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 35 publications
2
57
2
1
Order By: Relevance
“…The large heritability for the Control scale is surprising given other studies have consistently reported that this scale is one of the least heritable of the FES scales. In fact, the average heritability rating from the other studies (i.e., Bouchard and McGue, 1990;Hur and Bouchard, 1995;Jang et al, 2001;Plomin et al, 1988Plomin et al, , 1989Vernon et al, 1997) is only 0.09, considerably smaller than our heritability estimate of 0.46.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The large heritability for the Control scale is surprising given other studies have consistently reported that this scale is one of the least heritable of the FES scales. In fact, the average heritability rating from the other studies (i.e., Bouchard and McGue, 1990;Hur and Bouchard, 1995;Jang et al, 2001;Plomin et al, 1988Plomin et al, , 1989Vernon et al, 1997) is only 0.09, considerably smaller than our heritability estimate of 0.46.…”
Section: Discussioncontrasting
confidence: 51%
“…The acceptance factors were found to be more heritable (h 2 =0.38 and h 2 =0.19, respectively) than the control factor (h 2 =0.11), although the control factor was somewhat heritable. Jang et al, (2001) studied adult reared-together twins' retrospective responses using the FES. Although they did not factor analyze the FES scales, they did find that the scales that typically belong to the control factor (e.g., Control, Moral-Religious Emphasis, and Organization) had nonsignificant heritabilities, whereas the scales typically belonging to the acceptance factor (e.g., Cohesion, Achievement Orientation, Intellectual/Cultural Orientation, Active/ Recreational Orientation) were significantly heritable.…”
mentioning
confidence: 99%
“…We have also assessed our participants' perceptions of the family environment (e.g., using the Family Environment Scales; Moos & Moos, 1994), their school environment (e.g., Classroom Environment Scale; Moos & Moos, 1994), sibling interactions and parental preferences (e.g., Sibling Inventory of Differential Experience; Daniels & Plomin, 1985), and how each participant characteristically responds to environmental events (e.g., Environmental Response Inventory; McKechnie, 1974). These data are useful in testing models of personality trait and disorder development such as gene-environment interaction and correlation (Jang et al, 2001).…”
mentioning
confidence: 99%
“…Las investigaciones indican que un funcionamiento familiar positivo puede reducir las predisposiciones genéticas (Jang, Vernon, Livesley, Stein y Wolf, 2001). Tener una madre adicta o dos padres adictos aumenta el riesgo de posteriores problemas de desarrollo (Dube, Anda, Felitti, Croft, Edwards y Giles, 2001).…”
unclassified
“…Luthar and associates (1998) report similar risks in children of drug abusers, but conclude that maternal drug abuse per se is not as damaging to children's resilience as maternal stress, depression, and anxiety disorders (Luthar, D'Avanzo & Hites, 2005). Other research suggests that positive family functioning can reduce genetic predispositions (Jang, Vernon, Livesley, Stein, & Wolf, 2001). Having a mother who is an addict or two parents who are addicted increases their risk for later developmental problems (Dube, Anda, Felitti, Croft, Edwards & Giles, 2001).…”
mentioning
confidence: 99%